A New Three-Dimensional Subsulfide Ir2In8S with Dirac Semimetal Behavior - Khoury, Jason F; Rettie, Alexander J. E; Khan, Mojammel A; Ghimire, Nirmal J; Robredo, Iñigo; Pfluger, Jonathan E; Pal, Koushik; Wolverton, Chris; Bergara, Aitor; Jiang, J. S; Schoop, Leslie M; Vergniory, Maia G; et al. (Journal of the American Chemical Society, 2019)
Dirac and Weyl semimetals host exotic quasiparticles with unconventional transport properties, such as high magnetoresistance and carrier mobility. Recent years have witnessed a huge number of newly predicted topological semimetals from existing databases; however, experimental verification often lags behind such predictions. Common reasons are synthetic difficulties or the stability of predicted phases. Here, we report the synthesis of the type-II Dirac semimetal Ir2In8S, an air-stable compound with a new structure type. This material has two Dirac crossings in its electronic structure along the Γ–Z direction of the Brillouin zone. We further show that Ir2In8S has a high electron carrier mobility of ∼10 000 cm2/(V s) at 1.8 K and a large, nonsaturating transverse magnetoresistance of ∼6000% at 3.34 K in a 14 T applied field. Shubnikov de-Haas oscillations reveal several small Fermi pockets and the possibility of a nontrivial Berry phase. With its facile crystal growth, novel structure type, and striking electronic structure, Ir2In8S introduces a new material system to study topological semimetals and enable advances in the field of topological materials.